Implementasi Fitur Sinkronisasi Basis Data Pada Aplikasi Monitoring Keuangan Pada Wilayah Dengan Keterbatasan Jaringan Internet - Aldi Setiawan; Danny Sebastian; Kristian Adi Nugraha (Fakultas Teknologi Informasi, 2022)
Tobacco farmers in Central Java often have commercial relationships with many parties. One of the actions of the process is the process of accounts payable between farmers and traders. The difficulty that arises from this process is when recording debt data every day. Often farmers in these areas still use paper as a medium to store debt data. Of course, this can be a problem when the paper is lost and the debt data that is owned is also lost. So it is proposed to make a debt recording application on a mobile device so that it is easy to carry and the stored data is not easily lost. However, a new problem arises, namely when the mobile device is not connected to the internet network whether debt data can still be stored, seeing that the area where the farmer is located does not have an adequate internet network. Based on the problems encountered, it is proposed to create a synchronization algorithm that can handle when the mobile device is not connected to the internet network. The data will be synchronized on the website application created, so that the data entered by farmers when they are not connected to the internet network can be stored properly without fear of losing the debt data. Tests are carried out using white box testing and actual testing. For the white box testing that was tested on the algorithm that has been made, the results show that the algorithm created has a low risk level and a 5 percent improvement probability. For the actual tests carried out, based on the results obtained, each test scenario can be tested well and produce good results. So it can be concluded that the algorithm that has been made is feasible to be applied to mobile devices.